Method for verifying the quality of coarse aggregate for ultra-high-strength concrete.
Patent Information
- Application Number
- JP2025064323
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-22
AI Technical Summary
【0017】 本発明によれば、粗骨材が超高強度コンクリートに適した強度を有しているかどうかを早期に確認することができる。
Smart Images

Figure 2026170655000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a method for confirming the quality of coarse aggregate required for ultra-high-strength concrete, specifically its suitability for strength. [Background technology]
[0002] In recent years, with the increasing demand for skyscrapers, particularly in urban areas, 120 N / mm 2 Furthermore, 150 N / mm 2 Ultra-high-strength concrete requiring design strengths of the above is used. From the perspective of the compressive strength of concrete, the strength of the coarse aggregate, which makes up a large portion of the volume of the concrete, affects the compressive strength of the concrete.
[0003] However, JIS A 5005 (Crushed stone and crushed sand for concrete), which concerns coarse aggregate used in concrete, does not specify any requirements regarding strength, nor does it mandate strength verification.
[0004] On the other hand, the British Standards for Crushing (BS812-110) specifies a "crushing test" to evaluate aggregate strength based on the particle size (crushing value) of coarse aggregate crushed by loading with a pressure machine. In Japan, a method has been proposed to simplify the crushing test of the BS standard and evaluate aggregate strength using a simplified crushing value. In addition, a method has been proposed to evaluate aggregate strength by performing a compressive strength test on core specimens of rock taken from raw ore. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] JIS A 5005 "Crushed stone and crushed sand for concrete" [Non-Patent Document 2] British Standard BS812: Part110: 1990 [Overview of the project] [Problems that the invention aims to solve]
[0006] As mentioned above, JIS A 5005 (Crushed stone and crushed sand for concrete) does not contain any provisions regarding the strength of coarse aggregate, so simply conforming to JIS does not guarantee a design strength of 150 N / mm². 2 It is not possible to determine whether the coarse aggregate has sufficient strength to be suitable for ultra-high-strength concrete of that grade.
[0007] Furthermore, the inventors stated that the design strength is 150 N / mm². 2 When we examined the relationship between the compressive strength of ultra-high-strength concrete of a certain grade and the simple crushing value of the coarse aggregate used in it, we found no clear correlation. Therefore, it is difficult to determine the suitability of coarse aggregate based on the simple crushing value. Furthermore, when the inventors conducted compressive strength tests on core specimens of rock taken from raw materials in accordance with JGS 2521 (Uniaxial Compression Test Method for Rocks), it was confirmed that the compressive strength of the rock is greatly affected by weak parts such as spoil and joints within the rock. Therefore, it is also difficult to determine the suitability of coarse aggregate based on the strength test of the rock alone.
[0008] Therefore, the present invention aims to provide a method for early confirmation of whether coarse aggregate has the quality suitable for ultra-high-strength concrete (a method for confirming the suitability of coarse aggregate for ultra-high-strength concrete). [Means for solving the problem]
[0009] To achieve the above objective, the method for confirming the suitability of coarse aggregate for ultra-high-strength concrete according to the present invention comprises: a standard preparation test step in which a compressive strength test is performed on a specimen that has been cured under standard conditions for a first period to harden the concrete, and the standard compressive strength of the specimen is measured; a heated preparation test step in which a compressive strength test is performed on a specimen that has been cured under higher temperatures than the standard curing for a second period shorter than the first period, and the heated compressive strength of the specimen is measured; and the standard prepared test step in which the standard compressive strength of the specimen measured in the standard preparation test step is measured The method comprises: a calculation step of calculating a relational expression showing the correlation between the standard compressive strength and the heated compressive strength based on the semi-compressive strength and the heated compressive strength measured in the heated preparation test step; a determination value setting step of setting the heated compressive strength corresponding to the target value for the standard compressive strength in the relational expression as a determination value; a main test step of performing a compressive strength test on a test specimen made of concrete in which the coarse aggregate to be checked and the predetermined other materials are mixed according to the predetermined mix conditions, and which has been cured under heated conditions for approximately the same period as the second period and under approximately the same conditions as the heated preparation test step, and measuring the compressive strength of the test specimen; and a main determination step of determining the suitability of the coarse aggregate by comparing the measured value in the main test step with the determination value.
[0010] Furthermore, in the method for confirming the suitability of coarse aggregate for ultra-high-strength concrete according to the present invention, if the measured value of the compressive strength test is greater than the judgment value in the judgment step, the coarse aggregate may be judged as suitable.
[0011] Furthermore, in the method for confirming the suitability of coarse aggregate for ultra-high-strength concrete according to the present invention, the target value includes a first target value and a second target value that is greater than the first target value, and the judgment value includes a first judgment value that corresponds to the first target value and a second judgment value that corresponds to the second target value and is greater than the first judgment value, and in the judgment step, if the measured value of the compressive strength test is greater than the second judgment value, the coarse aggregate may be judged as suitable, while if the measured value of the compressive strength test is less than the first judgment value, the coarse aggregate may be judged as unsuitable.
[0012] Furthermore, the method for confirming the suitability of coarse aggregate for ultra-high-strength concrete according to the present invention may further include a retesting step in which, if the measured value in the main test step is greater than the first judgment value and less than the second judgment value, a compressive strength test is performed on a specimen made of concrete in which the coarse aggregate to be confirmed and the predetermined other materials are mixed according to the predetermined mixing conditions, and the specimen has been cured for approximately the same period as the second period under approximately the same conditions as the heating preparation test step, and the compressive strength of the specimen is measured; and a re-determination step in which the suitability of the coarse aggregate is determined by comparing the measured value in the retesting step with the judgment value.
[0013] Furthermore, in the method for confirming the suitability of coarse aggregate for ultra-high-strength concrete according to the present invention, if the measured value of the compressive strength test is greater than the second determination value in the re-evaluation step, the coarse aggregate may be determined to be suitable.
[0014] Furthermore, in the method for confirming the suitability of coarse aggregate for ultra-high-strength concrete according to the present invention, if the measured value of the compressive strength test is smaller than the second judgment value in the re-evaluation step, the coarse aggregate may be judged as unsuitable.
[0015] Furthermore, in the method for confirming the suitability of coarse aggregate for ultra-high-strength concrete according to the present invention, in the judgment step described above, if the measured value of the compressive strength test is smaller than the judgment value, the coarse aggregate may be judged as unsuitable.
[0016] Further, in the method for confirming the quality suitability of coarse aggregate for ultra-high strength concrete according to the present invention, the curing of the specimen in the heating preparation test step may have appropriate preheating time and high-temperature holding time. Effects of the Invention
[0017] According to the present invention, it is possible to confirm at an early stage whether the coarse aggregate has strength suitable for ultra-high strength concrete. Brief Description of the Drawings
[0018] [Figure 1] It is an explanatory diagram showing an example of temperature transition related to heating accelerated curing. [Figure 2] It is a diagram showing the results of a high-temperature curing time confirmation experiment. [Figure 3] It is a graph showing the correlation between the compressive strength related to heating accelerated curing and the compressive strength related to standard curing. [Figure 4] It is a table showing estimated values of compressive strength related to heating accelerated curing corresponding to various target values of compressive strength related to standard curing. [Figure 5] It is a diagram showing an example of an on-site suitability confirmation flow for coarse aggregate. Modes for Carrying Out the Invention
[0019] (First Embodiment) The following describes a method for confirming the suitability of coarse aggregate for ultra-high-strength concrete according to the first embodiment of the present invention (hereinafter simply referred to as the "quality suitability confirmation method") based on Figures 1 to 5. The quality suitability confirmation method according to this embodiment is a method for confirming whether a certain coarse aggregate is suitable for use in ultra-high-strength concrete that requires a predetermined compressive strength. In other words, the quality suitability confirmation method according to this embodiment can confirm whether a coarse aggregate that may be used in a certain ultra-high-strength concrete has the necessary quality for that ultra-high-strength concrete. The quality suitability confirmation method is performed before the coarse aggregate, which has been prepared as actual material, is delivered to the ready-mix concrete plant or used on site. In the following, ultra-high-strength concrete may be simply referred to as "concrete".
[0020] The quality compliance confirmation method according to the first embodiment includes a standard preparation test step (S1), a heating preparation test step (S2), a calculation step (S3), a judgment value setting step (S4), a main test step (S5), a main judgment step (S6), a retest step (S7), and a re-judgment step (S8). In the quality compliance confirmation method, the standard preparation test step (S1) and the heating preparation test step (S2) are performed first, followed by the calculation step (S3) → judgment value setting step (S4) → main test step (S5) → main judgment step (S6) → retest step (S7) → re-judgment step (S8).
[0021] The main test process (S5), the main judgment process (S6), the retest process (S7), and the re-judgment process (S8) are actual processes performed on coarse aggregate that can be delivered to a ready-mix concrete plant or used on-site. On the other hand, the standard preparation test process (S1), the heating preparation test process (S2), the calculation process (S3), and the judgment value setting process (S4) are preparatory processes performed using various types of coarse aggregate prepared separately from the coarse aggregate that can be delivered to a ready-mix concrete plant.
[0022] Furthermore, as will be described later, in the standard preparation test process (S1), the heated preparation test process (S2), the main test process (S5), and the retest process (S7), specimens for measuring the compressive strength of concrete are prepared. The materials other than coarse aggregate (other materials) included in the specimens prepared in each process, the mix design conditions for the other materials, the dimensions of the specimens, the test equipment used for measurement, and the various conditions related to the compression test are all the same.
[0023] In the quality conformity confirmation method, the standard preparation test process (S1) and the heated preparation test process (S2) are performed first. The specimens used to measure the compressive strength of the concrete in the standard preparation test process (S1) and the heated preparation test process (S2) must be taken from concrete that was mixed at the same time. Therefore, in terms of the time relationship between the standard preparation test process (S1) and the heated preparation test process (S2), the standard preparation test process (S1) and the heated preparation test process (S2) are performed simultaneously (in parallel).
[0024] The standard preparation test process (S1) further comprises a standard preparation specimen preparation process (S11), a standard preparation curing process (S12), and a standard preparation measurement process (S13). In the standard preparation test process (S1), each process is carried out in the following order: standard preparation specimen preparation process (S11) → standard preparation curing process (S12) → standard preparation measurement process (S13).
[0025] In the standard preparation specimen preparation process (S11), specimens (standard preparation specimens) are prepared from concrete mixed under predetermined mixing conditions, containing predetermined materials including multiple types of coarse aggregate prepared for calculating the strength correlation formula described later. In the standard preparation curing process (S12), the standard preparation specimens prepared in the standard preparation specimen preparation process (S11) are subjected to standard curing for a first period to allow them to harden. In the standard preparation measurement process (S13), a compressive strength test is performed on the standard preparation specimens that have been standard-cured in the standard preparation curing process (S12), and the compressive strength of the standard preparation specimens (standard preparation compressive strength) is measured. The specific details of the first period and standard curing can be set as appropriate. The specific details of the first period and standard curing (examples) will be described later.
[0026] The heating preparation test process (S2) further comprises a heating preparation specimen preparation process (S21), a heating preparation curing process (S22), and a heating preparation measurement process (S23). In the heating preparation test process (S2), each process is carried out in the following order: heating preparation specimen preparation process (S21) → heating preparation curing process (S22) → heating preparation measurement process (S23).
[0027] In the heating preparation specimen preparation process (S21), specimens (heating preparation specimens) are prepared from concrete mixed under predetermined mix conditions, containing predetermined materials including multiple types of coarse aggregate prepared for calculating the strength correlation formula described later. As mentioned above, the heating preparation specimen preparation process (S21) is carried out simultaneously with the standard preparation specimen preparation process (S11), using the same concrete mixed in the standard preparation specimen preparation process (S11).
[0028] In the heating preparation curing process (S22), the heating preparation specimens prepared in the heating preparation specimen preparation process (S21) are cured for a second period shorter than the first period, under conditions higher than standard curing. In the heating preparation measurement process (S23), a compressive strength test is performed on the heating preparation specimens cured in the heating preparation curing process (S22), and the compressive strength of the heating preparation specimens (heating preparation compressive strength) is measured.
[0029] In the following, curing under conditions warmer than standard curing will be referred to as "heated accelerated curing." Heated accelerated curing is a curing method applied to accelerate the reaction between cement and water (harden the concrete) and to accelerate the development of compressive strength compared to standard curing. The specific details of the second period and heated accelerated curing can be set as appropriate, as long as the conditions are met that the second period is shorter than the first period and the heated accelerated curing is performed under conditions warmer than standard curing. The specific details of the second period and heated accelerated curing (examples) will be described later.
[0030] Furthermore, the standard preparation specimens and the heating preparation specimens are identical in dimensions and shape. In addition, the various conditions for the compressive strength test in the standard preparation measurement process (S13) and the various conditions for the heating preparation measurement process (S23) are identical. In other words, although the standard preparation test process (S1) and the heating preparation test process (S2) differ in curing period and method, they are performed simultaneously (in parallel) on specimens taken from the same concrete, under the same conditions except for the curing period and method.
[0031] In the calculation process (S3), a relational expression (hereinafter referred to as the "strength correlation expression") showing the correlation between the standard preparation compressive strength and the heated preparation compressive strength is calculated based on the standard preparation compressive strength measured in the standard preparation test process (S1) and the heated preparation compressive strength measured in the heated preparation test process (S2). The strength correlation expression is a relational expression used to set the judgment value in the judgment value setting process (S4), as will be described later. Details of the strength correlation expression will be described later.
[0032] In the judgment value setting step (S4), a judgment value for the strength of the concrete containing the coarse aggregate to be used is set based on the strength correlation formula calculated in the calculation step (S3) and the target values for compressive strength of the concrete produced in the first period and standard curing in the standard preparation test step (S1). The judgment value is used in the main judgment step (S6) and the re-judgment step (S8). The judgment value setting step (S4) will now be explained in detail.
[0033] The target compressive strength value for concrete containing the coarse aggregate to be used is an index or standard value set to guarantee and ensure the compressive strength of the concrete. This target value is based on concrete that has undergone the same curing period (first period) and curing method (specifications related to standard curing) as in the standard preparation test process (S1). In other words, the target value is the index or standard compressive strength for concrete cured under certain conditions.
[0034] In the first embodiment, the target values include a first target value and a second target value that is higher than the first target value. Specifically, the first target value is composed of the mix design strength (Fm). The second target value is composed of the average value of the mix design strength (Fm) and the mix design strength (F). Note that "mix design strength" is the target average compressive strength when determining the mix design of concrete, and "mix design strength" is the minimum compressive strength that a standard-cured specimen of the concrete must meet at a predetermined management age. The mix design strength is determined by adding twice the standard deviation of the compressive strength to the mix design strength so as to be sufficiently safe relative to the mix design strength.
[0035] Furthermore, there are two judgment values: a first judgment value corresponding to the first target value and a second judgment value corresponding to the second target value. Specifically, in the strength correlation equation calculated in the calculation process (S3), the first judgment value is the heating preparation compressive strength when the standard preparation compressive strength is the first target value, and the second judgment value is the heating preparation compressive strength when the standard preparation compressive strength is the second target value. As described later, the strength correlation equation is represented by a straight line with a positive slope, so the second judgment value is higher than the first judgment value, representing a relatively stricter, or in other words, safer standard for compressive strength.
[0036] The main test process (S5) further comprises the process of preparing the test specimen (S51), the curing process (S52), and the measurement process (S53). In the main test process (S5), each process is carried out in the order of the process of preparing the test specimen (S51) → curing process (S52) → measurement process (S53).
[0037] In the main test specimen preparation process (S51), test specimens (main test specimens) are prepared (taken) from concrete mixed with specified materials, including coarse aggregate intended for use and subject to confirmation by the quality suitability confirmation method, in other words, the coarse aggregate intended for use, under specified mix conditions. Here, the other materials involved in the main test specimen preparation process (S51) have the same quality as the other materials involved in the standard preparation test process (S1) and the heated preparation test process (S2). Furthermore, the mix conditions for the other materials involved in the main test specimen preparation process (S51) are the same as the mix conditions for the other materials involved in the standard preparation test process (S1) and the heated preparation test process (S2).
[0038] In the main curing process (S52), the test specimens prepared in the main test specimen preparation process (S51) are subjected to accelerated heating and curing for the second period, in the same manner as the heating preparation and curing process (S22). In the main measurement process (S53), a compressive strength test is performed on the test specimens cured in the main curing process (S52), and the compressive strength (main compressive strength) of the test specimens is measured.
[0039] Although the various conditions for accelerated heating in the main curing process (S52) and the various conditions for accelerated heating in the preparatory heating curing process (S22) are the same, in the following, the accelerated heating in the main curing process (S52) will be referred to as "main accelerated heating curing," and the accelerated heating in the preparatory heating curing process (S22) will be referred to as "preparatory accelerated heating curing."
[0040] In the main determination step (S6), the suitability of the coarse aggregate is determined by comparing the measured value of the compressive strength test (main compressive strength) in the main measurement step (S53) with the determination value. Here, the main determination step (S6) will be explained in detail.
[0041] As mentioned above, there are two judgment values: a first judgment value and a second judgment value. In this judgment process (S6), if the measured value is equal to or greater than the second judgment value, the coarse aggregate contained in this concrete is judged to be compliant, and the quality compliance confirmation method is terminated. In other words, the coarse aggregate may be used in ultra-high-strength concrete. On the other hand, in this judgment process (S6), if the measured value is less than the first judgment value, the coarse aggregate contained in this concrete is judged to be uncompliant, and the quality compliance confirmation method is terminated. In other words, the coarse aggregate should not be used in ultra-high-strength concrete.
[0042] Furthermore, in this judgment process (S6), if the measured value is greater than or equal to the first judgment value but less than the second judgment value, the coarse aggregate contained in this concrete is judged to be neither compliant nor non-compliant (the judgment of compliance is suspended), and the process proceeds to the retesting process (S7).
[0043] The retesting process (S7) further comprises a retest specimen preparation process (S71), a recuring process (S72), and a remeasurement process (S73). In the retesting process (S7), each process is carried out in the following order: retest specimen preparation process (S71) → recuring process (S72) → remeasurement process (S73).
[0044] In the retest specimen preparation process (S71), specimens (retest specimens) are prepared under the same conditions as in the main test specimen preparation process (S51). In the recuring process (S72), the retest specimens prepared in the retest specimen preparation process (S71) are subjected to accelerated heating and curing for a second period, under the same conditions as in the heating preparation and curing process (S22). In the remeasurement process (S73), a compressive strength test is performed on the retest specimens cured in the recuring process (S72), and the compressive strength (recompression strength) of the retest specimens is measured.
[0045] In the re-evaluation step (S8), the suitability of the coarse aggregate is determined by comparing the measured value of the compressive strength test (re-compression strength) in the re-measurement step (S73) with the judgment value. The re-evaluation step (S8) will now be explained in detail.
[0046] In the re-evaluation step (S8), if the measured value is equal to or greater than the second judgment value, the coarse aggregate contained in this concrete is judged to be compliant, and the quality compliance verification method is terminated. In other words, the coarse aggregate may be used in ultra-high-strength concrete. On the other hand, in the re-evaluation step (S8), if the measured value is less than the second judgment value, the coarse aggregate contained in this concrete is judged to be uncompliant, and the quality compliance verification method is terminated. In other words, the coarse aggregate should not be used in ultra-high-strength concrete.
[0047] Next, various examples of the quality suitability confirmation method of the present invention will be described. However, the quality suitability confirmation method of the present invention is not limited to the following examples.
[0048] (Examples relating to concrete and test specimens) For example, the other materials used in the standard preparation specimens, heating preparation specimens, main test specimens, and retest specimens include a special cement mixed with silica fume for ultra-high-strength concrete. Furthermore, the water-to-binder ratio (W / B) of this concrete is 13.0-16.0%. The specimen shape is a φ100mm x 200mm cylinder in accordance with JIS A 1132 (Method for preparing concrete strength test specimens). Note that a water-to-binder ratio (W / B) of 13.0-16.0% corresponds to a strength of 150 N / mm². 2 This is the water-to-binder ratio for ultra-high-strength concrete of a certain grade.
[0049] (Examples of methods for promoting curing through heating) Accelerated heating curing is carried out in a chamber where the room temperature can be controlled immediately after the preparation of the test specimen. The test specimen is sealed by covering the top surface with plastic wrap or the like. Figure 1 is an explanatory diagram showing the temperature progression related to accelerated heating curing. As shown in Figure 1, accelerated heating curing consists of four stages: pre-curing, heating, high-temperature curing, and cooling. High-temperature curing is the main curing in accelerated heating curing, and pre-curing is a supplementary curing that precedes it. Heating is done to slowly transition from pre-curing to high-temperature curing, and cooling is done to slowly transition from high-temperature curing to room temperature. Strictly speaking, in terms of the original meaning of curing, high-temperature curing is the curing of the concrete (test specimen), but the series of temperature histories from pre-curing to cooling, which includes high-temperature curing, is broadly considered curing.
[0050] The temperature for the initial curing stage is 20 degrees Celsius, the temperature for the high-temperature curing stage is 80 degrees Celsius, the rate of temperature change for heating is +20°C / h, and the rate of temperature change for cooling is -20°C / h. The duration for the initial curing stage is 10 hours, the duration for the high-temperature curing stage is 32 hours, the duration for heating is 3 hours, and the duration for cooling is 3 hours. Therefore, the second period (age) for accelerated heating curing is 48 hours.
[0051] Furthermore, it is desirable that the pre-curing time be appropriately determined so that high strength can be sufficiently achieved even when high-temperature curing is performed. Therefore, the inventor placed the strength test specimen in an insulated container, measured the temperature rise of the specimen due to cement hydration, and determined that 10 hours, the time at which the temperature rise began, was an appropriate pre-curing time. Furthermore, it is desirable that the high-temperature curing time be appropriately determined so that high strength can be sufficiently achieved even when high-temperature curing is performed. Therefore, the inventor conducted an experiment (high-temperature curing time confirmation experiment) to determine the time required for high-temperature curing. In the high-temperature curing time confirmation experiment, the inventor investigated the relationship between the time required for high-temperature curing (high-temperature curing time) and compressive strength for two types of coarse aggregate. Figure 2 is an explanatory diagram showing the results of the high-temperature curing time confirmation experiment.
[0052] The compressive strength of concrete containing the first type of coarse aggregate (Case 1) after 56 days of standard curing is approximately 150 N / mm². 2 The results were as follows: Based on this compressive strength, the compressive strength obtained after 8 hours and 12 hours of high-temperature curing at 80°C was insufficient, while the compressive strength obtained after 32 hours of high-temperature curing at 80°C was generally within the acceptable range. On the other hand, the compressive strength of the second type (Case 2) concrete containing coarse aggregate after 56 days of standard curing was approximately 180 N / mm². 2 The results showed that, based on the compressive strength, the compressive strength after 12 hours of high-temperature curing at 80°C was insufficient, while the compressive strength after 32 hours and 56 hours of high-temperature curing at 80°C was generally within the acceptable range. Based on these results, it is considered that when high-temperature curing is performed, the material must be aged for at least 32 hours.
[0053] (Examples of standard curing procedures) The standard curing method is underwater curing at 20°C ± 3°C, and the standard curing period (standard curing age) is 56 days.
[0054] (Examples of compressive strength testing) The compressive strength test will be conducted in accordance with JIS A 1108 (Method for testing the compressive strength of concrete).
[0055] (Examples of the strength correlation formula, target value, and judgment value) To determine the strength correlation formula, the inventors measured the compressive strength (standard preparation compressive strength) of several types of coarse aggregate under the standard curing (underwater curing) described in the aforementioned examples, and under the accelerated heating curing (heating preparation compressive strength) described in the aforementioned examples. The standard curing was performed at three different ages (7 days, 28 days, and 56 days). Furthermore, the test specimens used to measure the compressive strength were prepared under the same conditions as those used in the aforementioned examples.
[0056] Then, the standard preliminary compressive strength and the heating preliminary compressive strength for the same coarse aggregate were plotted on an xy coordinate plane for each material age under standard curing. Figure 3 is a diagram showing the relationship between the standard preliminary compressive strength and the heating preliminary compressive strength for each material age under standard curing. The horizontal axis (x value) of the xy plane illustrated in Figure 3 represents the heating preliminary compressive strength, and the vertical axis (y value) represents the standard preliminary compressive strength.
[0057] It should be noted that since the compressive strength varies from specimen to specimen, a set of three specimens prepared from a single batch of concrete mixed at the same time is used, and the average value of the compressive strengths of the three specimens is adopted as the compressive strength. To further supplement, a single batch of concrete is prepared for each type of coarse aggregate, and from this concrete, three specimens for heating accelerated curing, three specimens for standard curing with a material age of 7 days, three specimens for standard curing with a material age of 28 days, and three specimens for standard curing with a material age of 56 days are produced.
[0058] As shown in Figure 3, a certain correlation was confirmed for all curing periods. In addition, the correlation increases as the material age of standard curing increases. The strength correlation equation with the highest correlation for a material age of 56 days is y=1.0649x-5.7515. Therefore, the y value calculated by substituting the compressive strength of concrete actually produced by heating accelerated curing as the x value into this strength correlation equation is the estimated value of the compressive strength when the concrete is subjected to standard curing for 56 days.
[0059] In addition, the design reference strength of the ultra-high-strength concrete according to the above-described embodiment is 150 N / mm 2 , and the mix control strength is 157 N / mm 2 , the mix strength is 170 N / mm 2 , and the average value of the mix control strength and the mix strength is 163.5 N / mm 2 . Here, when the mix control strength is applied as the first target value and the average value of the mix control strength and the mix strength is applied as the second target value, the first target value is 150 N / mm 2 , and the second target value is 163.5 N / mm 2This is how it works. Then, the x-value calculated by applying these target values as y-values to the intensity correlation formula becomes the judgment value. Specifically, the first judgment value corresponding to the first target value is 157 N / mm². 2 Therefore, the second judgment value corresponding to the second target value is 163.5 N / mm². 2 This is the result. Figure 4 shows the mix design strength of ultra-high-strength concrete, the average value of the mix design strength and the mix design strength, and the relationship between the mix design strength and the estimated compressive strength in the heated accelerated curing method described above.
[0060] Therefore, in this embodiment, the on-site suitability confirmation flow for a coarse aggregate when it may be used as a material for ultra-high-strength concrete is as shown in Figure 5. This suitability confirmation flow corresponds to the main test process (S5), main judgment process (S6), retest process (S7), and re-judgment process (S8) of the quality suitability confirmation method.
[0061] As shown in Figure 5, first, the coarse aggregate and the other materials of the ultra-high-strength concrete according to the above-mentioned example are mixed according to the mix design conditions of the above-mentioned example, and a test specimen is prepared from the fresh concrete (test specimen preparation process (S51)). Then, the test specimen is subjected to accelerated heating curing according to the above-mentioned example (main curing process (S52)), and a compressive strength test is performed to measure the compressive strength (main measurement process (S53)). As a result, if the measured value is the second judgment value (163.5 N / mm²), 2 If the measured value is above the first judgment value (157 N / mm²), the coarse aggregate is judged to be suitable for use in ultra-high-strength concrete (this judgment process (S6)). In other words, the coarse aggregate can be delivered to the ready-mix concrete plant and used as ultra-high-strength concrete. On the other hand, if the measured value is above the first judgment value (157 N / mm²), the coarse aggregate is judged to be suitable for use in ultra-high-strength concrete (this judgment process (S6)). 2 If the aggregate is less than ), it is determined that the coarse aggregate is unsuitable for use in ultra-high-strength concrete (this determination step (S6)). In other words, the coarse aggregate cannot be delivered to the ready-mix concrete plant and cannot be used in ultra-high-strength concrete.
[0062] Furthermore, the measured value is the first judgment value (157 N / mm²). 2 ) or higher is the second judgment value (163.5 N / mm²). 2If the value is less than the second judgment value (S6), the coarse aggregate and the other materials of the ultra-high-strength concrete according to the above example are mixed again under the mix conditions according to the above example, and a test specimen is prepared from the fresh concrete (re-test specimen preparation step (S71)). Then, the test specimen is subjected to accelerated heating according to the above example (re-curing step (S72)), and a compressive strength test is performed to measure the compressive strength (re-measurement step (S73)). If the measured value is less than the second judgment value (163.5 N / mm²), 2 If the value is above the second judgment value (163.5 N / mm²), the coarse aggregate is judged to be suitable for use in ultra-high-strength concrete (re-evaluation process (S8)). On the other hand, if the measured value is above the second judgment value (163.5 N / mm²), the coarse aggregate is judged to be suitable for use in ultra-high-strength concrete. 2 If the value is less than ), the coarse aggregate is deemed unsuitable for use in ultra-high-strength concrete (re-evaluation process (S8)).
[0063] As described above, according to the quality suitability confirmation method of the first embodiment, a standard preparation test step (S1) is performed on a specimen that has been cured under standard conditions for a first period to harden the ultra-high-strength concrete made of multiple types of coarse aggregate and other materials mixed in a predetermined proportion, and the standard preparation compressive strength of the specimen is measured in advance. A heating preparation test step (S2) is performed on a specimen that has been heated and accelerated cured for a second period shorter than the first period, and the heating preparation compressive strength of the specimen is measured in advance. The standard preparation compressive strength measured in the standard preparation test step (S1) and the heating preparation test step ( The process includes: a calculation step (S3) to calculate a strength correlation formula showing the correlation between the standard preparation compressive strength and the heating preparation compressive strength based on the heating preparation compressive strength measured in S2; a judgment value setting step (S4) to set the heating preparation compressive strength corresponding to the target value for the standard preparation compressive strength in the strength correlation formula as the judgment value; a main test step (S5) to measure the compressive strength of a specimen that is made of concrete mixed with the coarse aggregate and other materials to be used (the material to be checked) in a predetermined mix, and has been heated and cured under accelerated conditions for the second period under the same conditions as the heating preparation test step (S2); and a main judgment step (S6) to determine the suitability of the coarse aggregate by comparing the measured value in the main test step (S5) with the judgment value. Before a certain coarse aggregate is used in concrete, especially ultra-high-strength concrete, the compressive strength of the concrete is measured after it has undergone accelerated heating curing to accelerate strength development, and also after it has undergone standard curing to ensure stable strength development. A strength correlation formula showing the correlation between these compressive strengths is calculated, and a judgment value is set based on the target value derived from the strength correlation formula. Therefore, when there are plans to use the coarse aggregate, the suitability of the compressive strength of the coarse aggregate (suitability for use in concrete) can be confirmed early by applying accelerated heating curing under the same conditions to a specimen containing the coarse aggregate. Furthermore, since the selection of coarse aggregates that may be included in concrete is performed, the safety and reliability of the structure can be improved.
[0064] In the quality suitability confirmation method according to the first embodiment, a general compressive strength test is performed, and no strength test specific to coarse aggregate is performed. Design standard strength: 150 N / mm² 2 It is known that in ultra-high-strength concrete of a certain grade, the strength characteristics of the coarse aggregate itself affect the compressive strength of the concrete. Therefore, by actually manufacturing ultra-high-strength concrete containing, for example, a special cement mixed with silica fume for ultra-high-strength concrete, with a water-to-battery ratio (W / B) of 13.0-16.0%, and verifying its compressive strength, it is possible to indirectly determine the compressive strength of the coarse aggregate. As a result, existing equipment and machinery can be used, which reduces costs compared to directly verifying the strength of the rock itself. Furthermore, by directly verifying the compressive strength of ultra-high-strength concrete, the suitability of the coarse aggregate can be determined more reliably.
[0065] Furthermore, according to the quality conformity confirmation method, in the main judgment process (S6) and the re-judgment process (S8), if the measured value is greater than the second judgment value, the coarse aggregate is judged to be conforming. Therefore, the delivery of coarse aggregate to ready-mix concrete plants and the shipment of concrete containing coarse aggregate to construction sites can be carried out smoothly, and the safety and reliability of structures can be further improved. In addition, according to the quality conformity confirmation method, the target values include a first target value and a second target value that is greater than the first target value, and the judgment values include a first judgment value that corresponds to the first target value and a second judgment value that is greater than the first judgment value and corresponds to the second target value, and in the main judgment process (S6), if the measured value is greater than the second judgment value, the coarse aggregate is judged to be conforming, while if the measured value is smaller than the first judgment value, the coarse aggregate is judged to be unconforming. Therefore, the delivery of coarse aggregate to ready-mix concrete plants, the shipment of concrete containing coarse aggregate to construction sites, and the cessation or suspension of these operations can be carried out smoothly, and the safety and reliability of structures can be further improved.
[0066] Furthermore, according to the quality suitability confirmation method, if the measured value in the judgment step (S6) is greater than the first judgment value and less than the second judgment value, the coarse aggregate and other materials are mixed again under predetermined mixing conditions, and a compressive strength test is performed on a specimen made from the fresh concrete and subjected to accelerated heating and curing under the same conditions as the heating preparation and curing step (S22). The method further includes a retest step (S7) in which the measured value of the compressive strength test is measured, and a re-judgment step (S8) in which the suitability of the coarse aggregate is determined by comparing the measured value with the judgment value. Therefore, it is possible to promote the use of coarse aggregate and further improve the safety and reliability of structures.
[0067] Furthermore, according to the quality conformity confirmation method, in the re-evaluation process (S8), if the measured value is greater than the second judgment value, the coarse aggregate is judged to be conforming. Therefore, the delivery of coarse aggregate to ready-mix concrete plants and the shipment of concrete containing coarse aggregate to construction sites can proceed smoothly, and the safety and reliability of structures can be further improved. Also, in the re-evaluation process (S8), if the measured value is smaller than the second judgment value, the coarse aggregate is judged to be unconforming. Therefore, the cessation or cancellation of the delivery of coarse aggregate to ready-mix concrete plants and the shipment of concrete containing coarse aggregate to construction sites can proceed smoothly, and the safety and reliability of structures can be further improved. In addition, according to the quality conformity confirmation method, the curing of the test specimen in the heating preparation test process (S2) has an appropriate pre-treatment time and high-temperature holding time. Therefore, even if high-temperature curing is applied to the test specimen, high strength is sufficiently developed, thus improving the reliability of the quality conformity confirmation method.
[0068] Although embodiments and examples of the quality suitability confirmation method according to the present invention have been described above, the present invention is not limited to the above embodiments and examples, and can be modified as appropriate without departing from the spirit of the invention.
[0069] For example, in the first embodiment described above, there are a first target value and a second target value. The first target value is set to the mix control strength, and the second target value is set to the average value of the mix control strength and the mix strength. However, the specific contents of the first and second target values may be changed as appropriate. For example, the average value of the mix control strength and the mix strength may be applied to the first target value, and the mix strength may be applied to the second target value, or the mix control strength may be applied to the first target value, and the mix strength may be applied to the second target value. Alternatively, compressive strengths other than the mix control strength, the mix strength, and the average value of the mix control strength and the mix strength may be applied to the first or second target value. However, as in the first embodiment, if the second target value is set to the average value of the mix control strength and the mix strength on the safe side, the probability of non-conformity will be smaller than if the mix strength is used, thus increasing the tolerance for coarse aggregate and maintaining a practical balance.
[0070] Furthermore, the target value and judgment value may be limited to one type, or to three or more types. If there is only one type of target value and judgment value, in the main judgment process (S6), if the measured value is equal to or greater than the judgment value, it is judged as conforming, while if the measured value is less than the judgment value, it is judged as non-conforming, and the retesting process (S7) and re-judgment process (S8) may not be performed. In this case, the entire quality conformity confirmation method can be expedited.
[0071] Furthermore, various conditions related to accelerated heating and curing (temperature, time, temperature change rate, etc.) may be appropriately changed within a range that allows for the early development of high strength.
[0072] Furthermore, the standard curing method and curing period may be appropriately modified depending on the target concrete's age, curing temperature, and tendency for increased compressive strength. In addition, the type of cement used in the concrete, in other words, the specific contents of other materials and the water-to-binder ratio of the concrete may also be appropriately modified.
[0073] Furthermore, in the first embodiment, the period and various conditions (temperature history) related to accelerated heating in the heating preparation test process (S2) and the period and various conditions (temperature history) related to accelerated heating in the main test process (S5) are completely identical. However, either one or both of the period and various conditions (temperature history) do not need to be completely identical, but may be approximately the same. The same applies to the retest process (S7). [Explanation of Symbols]
[0074] S1...Standard preparation test process, S2...Heating preparation test process, S3...Calculation process, S4...Judgment value setting process, S5...Main test process, S6...Main judgment process, S7...Retest process, S8...Rejudgment process
Claims
1. The concrete consists of multiple types of coarse aggregate and specified other materials mixed under specified mixing conditions, and the standard preparation test process involves performing a compressive strength test on a standard-cured specimen during the first period for the concrete to harden, and measuring the standard compressive strength of the specimen. A heating preparation test step involves performing a compressive strength test on a specimen that is made of concrete prepared by mixing the aforementioned multiple types of coarse aggregate and the aforementioned predetermined other materials under predetermined mixing conditions, and which has been cured for a second period shorter than the first period and at a higher temperature than the standard curing period, and measuring the heated compressive strength of the specimen, A calculation step to calculate a relational expression showing the correlation between the standard compressive strength and the heated compressive strength, based on the standard compressive strength measured in the standard preparation test step and the heated compressive strength measured in the heated preparation test step. A determination value setting step, in which the heated compressive strength corresponding to the target value for the standard compressive strength in the relational expression is set as the determination value, This test step involves measuring the compressive strength of a specimen that has been cured in a state where it has been heated for approximately the same period as the second period and under approximately the same conditions as the heating preparation test step, and the compressive strength of the specimen is measured. A method for confirming the suitability of coarse aggregate for ultra-high-strength concrete, comprising: a determination step of determining the suitability of the coarse aggregate by comparing the measured value in the main test step with the determination value.
2. In the aforementioned determination step, if the measured value of the compressive strength test is greater than the determination value, the coarse aggregate is determined to be suitable, as described in claim 1, for determining the suitability of the quality of coarse aggregate for ultra-high-strength concrete.
3. The aforementioned target values include a first target value and a second target value that is greater than the first target value. The aforementioned determination value includes a first determination value corresponding to the first target value, and a second determination value corresponding to the second target value that is greater than the first determination value. In the aforementioned determination step, if the measured value of the compressive strength test is greater than the second determination value, the coarse aggregate is determined to be suitable, while if the measured value of the compressive strength test is less than the first determination value, the coarse aggregate is determined to be unsuitable, as described in claim 1, for determining the suitability of coarse aggregate in quality.
4. If the measurement value in the main test process is greater than the first judgment value and less than the second judgment value, a retesting step is performed in which a compressive strength test is conducted on a test specimen made of concrete mixed with the coarse aggregate subject to confirmation and the specified other materials according to the specified mixing conditions, which has been cured under conditions of heating for approximately the same period as the second period and approximately the same conditions as the heating preparation test process, and the compressive strength of the test specimen is measured. The method for confirming the quality suitability of coarse aggregate for ultra-high-strength concrete according to claim 3, further comprising a re-determination step of determining the suitability of the coarse aggregate by comparing the measured value in the re-test step with the determination value.
5. In the re-evaluation step, if the measured value of the compressive strength test is greater than the second determination value, the coarse aggregate is determined to be suitable, as described in claim 4, for determining the suitability of the quality of coarse aggregate for ultra-high-strength concrete.
6. The method for determining the suitability of coarse aggregate for ultra-high-strength concrete according to claim 4, wherein in the re-evaluation step, if the measured value of the compressive strength test is smaller than the second determination value, the coarse aggregate is determined to be unsuitable.
7. In the aforementioned determination step, if the measured value of the compressive strength test is smaller than the determination value, the coarse aggregate is determined to be unsuitable, as described in claim 1, for determining the suitability of coarse aggregate for ultra-high-strength concrete.
8. A method for confirming the suitability of coarse aggregate for ultra-high-strength concrete according to any one of claims 1 to 7, wherein the curing of the test specimen in the heating preparation test step has an appropriate pre-treatment time and high-temperature holding time.